The role of leptin in indirectly mediating “somatic anxiety” symptoms in major depressive disorder - Zhu, Yue; Wei, Yange; Duan, Jia; Li, Jianing; Zhang, Ran; Sun, Jiaze; Wang, Pengshuo; Liu, Zhuang; Lv, Jing; Wei, Shengnan; Jiang, Xiaowei; Wang, Fei; et al. (Frontiers in Psychiatry, 2022)
Background: Leptin is a multifunctional hormone secreted from adipose tissue, which plays a core role in regulating energy intake and expenditure. Evidence has demonstrated that leptin receptors are located in brain areas involved in emotional processing, and major depressive disorder (MDD) is characterized by dysfunction of emotional processing. Taken together, these features suggest that leptin may play a potential role in the pathophysiology of MDD. However, the precise roles of leptin in modulating depressive symptoms in MDD remain unclear. Methods: Participants (18 drug-naïve MDD patients, 15 unaffected first-degree relatives of MDD patients [FDR-MDD], and 40 healthy controls) completed clinical assessments and provided blood samples for measurement of leptin levels. We evaluated the effect of leptin on clinical status (MDD or FDR-MDD) and symptomatic dimensionalities of MDD using mediation analysis. Results: We found that leptin was increased in MDD patients and this only predicted “somatic anxiety” symptoms. Furthermore, leptin was a significant and indirect mediator of the association between clinical status (MDD or FDR-MDD) and “somatic anxiety” symptoms. Conclusions: Our finding that leptin was a significant and indirect mediator of clinical status (MDD or FDR-MDD) and “somatic anxiety” symptoms suggests that leptin may indirectly affect somatic depressive symptoms in MDD. Our findings may provide a theoretical basis for novel clinical interventions in MDD.